Opposing effects of 5,7-DHT lesions to the core and shell of the nucleus accumbens on the processing of irrelevant stimuli - Nelson, Andrew J.D.; Thur, Karen E.; Marsden, Charles A.; Cassaday, Helen J. (Cambridge University Press, 2012)
There is good evidence that forebrain serotonergic systems modulate cognitive flexibility. Latent inhibition (LI) is a cross-species phenomenon which manifests as poor conditioning to a stimulus that has previously been experienced without consequence and is widely considered an index of the ability to ignore irrelevant stimuli. While much research has focused on dopaminergic mechanisms underlying LI, there is also considerable evidence of serotonergic modulation. However, the neuroanatomical locus of these effects remains poorly understood. Previous work has identified the nucleus accumbens (NAc) as a key component of the neural circuit underpinning LI and furthermore, this work has shown that the core and shell subregions of the NAc contribute differentially to the expression of LI. To examine the role of the serotonergic input to NAc in LI, we tested animals with 5,7-dihydroxytryptamine (5,7-DHT) lesions to the core and shell subregions on LI assessed under experimental conditions that produce LI in shams and subsequently with weak stimulus pre-exposure designed to prevent the emergence of LI in shams. We found that serotonergic deafferentation of the core disrupted LI whereas 5,7-DHT lesions to the shell produced the opposite effect and potentiated LI.